Determination of Domestic Prices of Milk and Wheat in Pakistan: Error in Estimation (Global Journal of Management and Business Research, 2012)
The domestic prices of traded goods in an open economy are a function of international prices and the levied tariff rates. The key question arising here is whether the domestic prices can be #x201C;estimated#x201D; from the information on international prices and the tariff rates given that the later two independent variables are determined out of the system? Some authors have #x201C;estimated#x201D; domestic prices from international prices and the tariff rates. However the estimation of domestic prices in such way has presented inaccurate estimates. Present study is an attempt to correct such failing in case of domestic prices of milk and wheat and strived to calculate instead of estimating the domestic prices in presence of two independently determined variables i.e. tariff rates and international prices.
Keywords: Domestic prices; Error in estimation; Credit goods